Antimicrobial activity of Bacillus velezensis strain PD9 secondary metabolite against methicillin resistant Staphylococcus aureus - Baharudin, Mohammad Malik Al-Adil (2021)
Methicillin resistant Staphylococcus aureus are opportunistic pathogen that are resistant towards many antibiotics particularly methicillin and penicillin class of antibiotic. Infections caused by MRSA have reached epidemic proportion globally. The rapid onset of resistance acquired by this bacterium reduces the efficacy of most commonly known antimicrobial drug; making it more difficult to treat. Therefore, there is an urgent need for an alternative therapeutic strategy and a continuous supply of antibiotic to combat the problem. Natural sources such as bacteria in the genus of Bacillus provide a promising potential for the exploration of anti-MRSA metabolites. Bacillus velezensis has been widely reported as bio-control agent in agriculture industry due to the vast spectrum of antimicrobial metabolites produced from this bacterium. However, there is lack of information available on the antimicrobial activity of this bacterium against MRSA. Thus, the aims of the study were to characterize antimicrobial activity and physicochemical feature of CFS against MRSA as well as to purify anti-MRSA metabolite(s) from B. velezensis strain PD9. In this study, bacteria initially identified as species belonged to the Bacillus amyloliquefaciens operational group were re-classified into specific species within the group based on housekeeping gene, gyrB. Cell-free supernatant (CFS) from B. velezensis strains were used for antimicrobial test using agar well diffusion assay against MRSA strains and various types of pathogenic bacteria. Antimicrobial activity of CFS from B. velezensis PD9 was characterised against MRSA ATCC 33742. Minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and MRSA growth inhibition effect were analysed. Physicochemical analyses of the strain PD9 CFS against MRSA ATCC 33742 were also determined. In this study, an antimicrobial peptide was purified from CFS of B. velezensis PD9 using solvent extraction method and silica gel column chromatography. The purified product was visualized using SDS-PAGE and zymogram. The purity of silica gel purified antimicrobial peptide was determined by using HPLC. Based on gyrB sequence analysis, 5 strains (PD9, B7, PU1, BP1 and L9) were classified as B. velezensis. CFS of all B. velezensis strains showed broad inhibitory activity against MRSA strains and several pathogenic Gram-negative and Gram-positive bacteria tested. Inhibitory activity of B. velezensis PD9 against MRSA ATCC 33742 were chosen for further analysis as it showed the biggest zone of inhibition (21.0 ± 0.4 mm). MIC and MBC values of B. velezensis PD9 CFS against MRSA ATCC 33742 obtained were 125 μl/ml. CFS of B. velezensis PD9 showed bactericidal activity against MRSA ATCC 33742 and were stable at various temperature (40 - 80 °C), pH (4-12), surfactant (Tween 20, Tween 80, SDS and Triton X-100) and metal ions (MgCI2, NaCI2, ZnNO3 and CuSO4) tested, but not in proteinase K; these properties resembled the characteristics of a peptide. Anti-MRSA metabolite was successfully concentrated using 1-butanol. Active fractions showing antimicrobial activity against MRSA ATCC 33742 were collected from silica gel column chromatography. The silica gel purified product was visualised on SDS-PAGE and zymogram. The size of the antimicrobial peptide obtained was approximately 5 kDa. The band with halo zone against MRSA ATCC 33742 was observed on zymogram. Single peak observed on HPLC chromagram indicated the purity of silica gel purified product. The present characterization reveals interesting properties of the antimicrobial peptide from B. velezensis PD9 which justifies its promising potential in controlling pathogenic MRSA strains. The antimicrobial peptide produced from B. velezensis PD9 might provide an alternative to combat the spread of MRSA infection in the future.